Frank Andonoplas : wedding consultant and event planner - Thompson, Kenneth R. (London : SAGE Publications: SAGE Business Cases Originals, 2022)
Event Planning is a generic term used to explain the various aspects of preparing for an event or activity, or an operation of a business or function of a business. Frank Andonoplas prefers the term event designer, which focuses on all elements involved in creating the ambiance of an environment to push an event beyond the expectations of the client, participant, and even the designer. This case focuses on the importance of event designing through an interview with Frank Andonoplas, who has received multiple awards and certifications in event designing, including the title of Master Wedding Planner, one of the few individuals to receive this honor in the United States. Students will be challenged to consider what the steps are in event planning, designing, and execution, and what tools can facilitate these processes.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Special events -- Management -- Case studies; Special events industry -- United States -- Case studies